2023
DOI: 10.3390/foods12132532
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Its Association with Lifestyle and Dietary Behaviors among Croatian Students during Two COVID-19 Lockdowns

Abstract: The present study aims to assess the diet quality, the relationship between diet quality and lifestyle, and the association of diet quality with body mass index and students’ field of study during COVID-19 lockdown periods (spring and winter) in 2020. Datasets were collected via an anonymous online self-reported questionnaire distributed during two time periods using social media. A total of 1939 Croatian students (82.4% women and 17.6% men) completed the questionnaire. Diet quality was assessed using the pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The time spent on screens increased more than twice among U.S. students [ 24 ], and it tripled among Croatian students [ 17 ]. A study demonstrated that increased screen time and reduced physical activity were associated with unhealthy dietary habits [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The time spent on screens increased more than twice among U.S. students [ 24 ], and it tripled among Croatian students [ 17 ]. A study demonstrated that increased screen time and reduced physical activity were associated with unhealthy dietary habits [ 28 ].…”
Section: Introductionmentioning
confidence: 99%